2018
DOI: 10.1038/sdata.2017.207
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of multi-signal and time-varying neural reconstructions

Abstract: Several efficient procedures exist to digitally trace neuronal structure from light microscopy, and mature community resources have emerged to store, share, and analyze these datasets. In contrast, the quantification of intracellular distributions and morphological dynamics is not yet standardized. Current widespread descriptions of neuron morphology are static and inadequate for subcellular characterizations. We introduce a new file format to represent multichannel information as well as an open-source Vaa3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…We previously confirmed that expression of the F-actin and microtubule transgene reporters did not themselves exert any effects on dendritic development (Das et al, 2017a). Live confocal imaging of agematched third instar larval mature da neuron Class I and Class IV arbors was performed as previously described (Das et al, 2017a;Nanda et al, 2018aNanda et al, , 2018b. Briefly, larvae were immersed in a 1:5 (v/v) diethyl ether to halocarbon oil on a cover slipped glass slide and neurons expressing fluorescent protein cytoskeletal reporter transgenes were visualized on a Zeiss LSM 780 confocal microscope.…”
Section: Drosophila Strains and Live Confocal Imagingmentioning
confidence: 71%
See 3 more Smart Citations
“…We previously confirmed that expression of the F-actin and microtubule transgene reporters did not themselves exert any effects on dendritic development (Das et al, 2017a). Live confocal imaging of agematched third instar larval mature da neuron Class I and Class IV arbors was performed as previously described (Das et al, 2017a;Nanda et al, 2018aNanda et al, , 2018b. Briefly, larvae were immersed in a 1:5 (v/v) diethyl ether to halocarbon oil on a cover slipped glass slide and neurons expressing fluorescent protein cytoskeletal reporter transgenes were visualized on a Zeiss LSM 780 confocal microscope.…”
Section: Drosophila Strains and Live Confocal Imagingmentioning
confidence: 71%
“…Microtubules and F-actin have long been implicated in neurostructural plasticity; however, their exact roles have not been fully elucidated due to the lack of their simultaneous quantification across the entirety of the neural arbor. With the use of the newly developed multi-signal reconstruction system (Nanda et al, 2018a), we quantified the arbor-wide microtubule and F-actin distributions from live images of fruit fly sensory neurons. Analysis of cytoskeletal distribution revealed the association of local microtubule with dendritic elongation (arbor size) and of local F-actin with dendritic branching (arbor complexity).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To annotate the reconstructions with proper metadata, the repository administrators have also been inviting data contributors to provide suitable information through a semi-structured Excel spreadsheet [33]. While the ecosystem of neuronal reconstructions has coalesced around a simple data standard for over two decades [30], selection and interpretation of metadata concepts remain highly variable and inconsistent. Thus, for every new dataset, a team of trained curators must validate or reconcile the author-provided information, complemented as needed by the associated publication, with the metadata schema and preferred nomenclature of the database.…”
Section: Introductionmentioning
confidence: 99%